2009
DOI: 10.1002/jor.20566
|View full text |Cite
|
Sign up to set email alerts
|

Rotating three‐dimensional dynamic culture of adult human bone marrow‐derived cells for tissue engineering of hyaline cartilage

Abstract: The method of constructing cartilage tissue from bone marrow-derived cells in vitro is considered a valuable technique for hyaline cartilage regenerative medicine. Using a rotating wall vessel (RWV) bioreactor developed in a NASA space experiment, we attempted to efficiently construct hyaline cartilage tissue from human bone marrow-derived cells without using a scaffold. Bone marrow aspirates were obtained from the iliac crest of nine patients during orthopedic operation. After their proliferation in monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Subcutaneous transplantation was also used in a part of this study aimed at future clinical use, since the primary indication for elastic cartilage regeneration will be craniofacial deformities, as noted in our previous article (9). As controls, CPCs from the same donor were also subjected to conventional pellet culture (28). Approximately 2 × 10 6 cells were placed in a 15-ml polypropylene tube and centrifuged at 500 g for 5 minutes at 4°C.…”
Section: Transplantation In Vivomentioning
confidence: 99%
“…Subcutaneous transplantation was also used in a part of this study aimed at future clinical use, since the primary indication for elastic cartilage regeneration will be craniofacial deformities, as noted in our previous article (9). As controls, CPCs from the same donor were also subjected to conventional pellet culture (28). Approximately 2 × 10 6 cells were placed in a 15-ml polypropylene tube and centrifuged at 500 g for 5 minutes at 4°C.…”
Section: Transplantation In Vivomentioning
confidence: 99%
“…It was reported that the large-sized tissue-engineered constructs were cultured, using roating wall vessel (RWV) [17]. When the RWV was used to culture the mesenchymal stem cells, favorable results of cartilage regeneration have been found [18]. However, the floating culture requires specific devices, a problem remains with regard to transport, and, basically, only rounded shapes, such as spherical and circular shapes, can be used because mechanical forces can be spread out.…”
Section: Discussionmentioning
confidence: 99%
“…Ohyabu and colleagues [30] used cultured rabbit BMSCs without a scaffold, and obtained cartilaginous constructs with higher expression of GAG and Col II compared to pellets. Human BMSCs cultured in an RWV without a scaffold, resulted in statistically signi icantly higher concentrations of GAG and Col II compared to pellets [31]. Yoshioka and colleagues [32] reported successful regeneration of cartilage in osteochondral-defective Japanese white rabbits using cartilaginous constructs obtained from culturing BMSCs.…”
Section: Rotating Wall Vesselmentioning
confidence: 99%